The Design of Automatic Powder Packaging Tools Based on Atmega 16 Microcontroller on Home industry - Bagus Wahyudi; Koko Joni; Riza Alfita; Miftachul Ulum (Merdeka Malang University, 2022)
In production, packaging is an essential factor. Especially if the product is in the form of food, the function of the packaging is to protect it from sunlight, dust, and other damage. There are still many who use the manual method in the home industry. The process still requires many human resources.For this reason, the design of an automatic powder packaging device based on the Atmega 16 microcontroller was made. This tool serves to package flour (flour, sugar, and coffee) packaged automatically using a microcontroller as the brain of the device. The initial packaging method was to put the powder in each container. Then the powder will come out automatically according to the input of the type of powder and the desired weight of the operator via the keypad. Then the powder enters the dose that Loadcell has installed as a weight detector displayed on the LCD. After the weight reaches the set point, the powder will enter the package. The package that has been filled with powder will be pressed using a sealer. From the tests carried out, the percentage of success reached 70%.